2004
DOI: 10.1111/j.1600-0609.2004.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of vascular endothelial growth factor immunoexpression in the context of adverse standard prognostic factors in multiple myeloma

Abstract: Our findings underline the frequent expression of VEGF in advanced-stage MM and the greater prognostic information of simple and readily available factors, namely plasmablastic morphology and elevated LDH. Moreover, despite the absence of prognostic importance in multivariate analysis, VEGF and its receptors remain promising therapeutic targets in MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 30 publications
(35 reference statements)
3
12
0
Order By: Relevance
“…We identified VEGF immunoreactivity in 79.7% bone marrow biopsy specimens. These data are in accordance with the results of previous immunohistochemical studies in myeloma patients [18][19][20][21][22][23]. Nevertheless, there are conflicting data regarding correlation between VEGF expression and clinicopathological parameters.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…We identified VEGF immunoreactivity in 79.7% bone marrow biopsy specimens. These data are in accordance with the results of previous immunohistochemical studies in myeloma patients [18][19][20][21][22][23]. Nevertheless, there are conflicting data regarding correlation between VEGF expression and clinicopathological parameters.…”
Section: Discussionsupporting
confidence: 95%
“…Nevertheless, there are conflicting data regarding correlation between VEGF expression and clinicopathological parameters. Some authors have found association between VEGF expression and proliferative activity [20], plasmablast morphology, low hemoglobin, and high grade of angiogenesis [21]. On the contrary, we did not find significant correlation between VEGF expression and selected clinicopathological parameters, which is in accordance with the results of Choi et al [18].…”
Section: Discussionsupporting
confidence: 88%
“…That is probably the reason why VEGF and bFGF levels have been found to be increased in MM patients and correlate with survival. 17,18,32,33 In our cohort of patients with refractory/relapsed MM, serum levels of both VEGF and bFGF were increased in comparison with the values among normal controls. In addition, MVD values were also increased in this cohort of patients compared to controls who had NHL with no bone marrow involvement, confirming the role of angiogenesis in myeloma biology.…”
Section: Discussionmentioning
confidence: 92%
“…High expression of VEGF in myeloma cells or increased serum VEGF levels in patients with myeloma is linked with aggressive disease and resistance to chemotherapy, suggesting that the VEGF pathway may be a critical therapeutic target [20,21]. VEGF is also expressed in Hodgkin lymphomas [22] and increased serum levels in these patients have been reported [23].…”
Section: Discussionmentioning
confidence: 95%